A Facile Route to Synthesis of Hierarchically Porous Carbon via Micelle System for Bifunctional Electrochemical Application - Hou, Xiaojian; Song, Yi; Zhao, Yueju; Li, Wenxiu; Guo, Zanwu; Tang, Shaoru; Ma, Yanan; Sun, Ruiwen; Wang, Qian; Li, Wei (Frontiers in Chemistry, 2021)
Well-ordered hierarchically porous carbon (HPC) nanomaterials have been successfully synthesized by a facile, efficient and fast heated-evaporation induced self-assembly (HISA) method. A micelle system was employed as template for the first time to fabricate HPC by using HISA method. Various surfactants, including triblock copolymer Pluronic F127, P123, F108 and cationic CTAB, were used to reveal the formed architecture of the as-prepared HPCs. Transmission electron microscopy (TEM), X-ray diffraction (XRD), N2 adsorption-desorption isotherm, and Fourier transform infrared (FTIR) measurements were conducted to investigate the structure and components of the obtained HPCs. The HPC sample prepared with F127 possesses larger specific surface area, suitable pore size and well-ordered mesoporous structure for the application of electrodes in the fields of energy storage and conversion system. By doping metallic oxide MnO2, the obtained composites as electrodes of supercapacitor exhibited excellent electrochemical activity and stability. Moreover, the obtained MnO2/HPC sample could also be applied in the fields of oxygen reduction reaction (ORR). This versatile approach makes the HPC material a strong candidate for the mass industrial production in the electrochemical application through a facile and fast route.